Voice of Reason: Why the Left and Right Are Wrong - Owens Ronn (Wiley, 2004)
Voice of Reason is a breath of fresh air in today’s toxic political climate, offering a positive message in dark times: that with reason, common sense, and pragmatism, we can find common ground between all Americans–left, right, and center. If you’re sick of the hyperactive bleating of the Ann Coulters and Michael Moores, and you’re ready for a straightforward and fair discussion of today’s biggest issues, there’s only one Voice of Reason out there.